Analysis of Bus Service Reliability Using A VL Data: Case Study of the City of Koper - Paliska, Dejan; Kolenc, Jurij (Promet - Traffic&Transportation, 2008)
This article uses a statistical approach to examine the bussystem reliability in the city of Koper. Four statistical modelswere developed using OLS to explain the effect of different variableson system reliability. The results indicate that the operatorhas no serious problems with maintaining system reliability,and that the most important factors affecting reliability are delayvariation at previous time point and cumulative distancefrom route origin. Although the available data were not complete,the results presented appear to be accurate. The resultsobtained from the developed models could be used to estimatebus delays under various conditions.